Pengaruh Sektor Pariwisata dan Investasi terhadap Pendapatan Asli Daerah Kabupaten di Luar SARBAGITA - Ni Putu Dewi Prawerti; I Wayan Priyana Agus Sudharma (Pusat Riset dan Inovasi Nasional, 2026)
The tourism sector is a primary driver of Bali's economy, particularly in the SARBAGITA region (Denpasar, Badung, Gianyar, and Tabanan), which contributes the largest Regional Original Income (PAD). In contrast, areas outside SARBAGITA, including Jembrana, Buleleng, Karangasem, Bangli, and Klungkung, have more tourist attractions but contribute less to PAD, indicating a development gap. This study analyzes the influence of tourism and investment sectors on PAD in regencies outside SARBAGITA during 2016–2022. Independent variables include tourist visits, hotels, restaurants, and investment, while PAD is the dependent variable. A quantitative panel data approach using Panel Least Squares (PLS) regression was applied. Results show that tourist visits and investment have no significant partial effect on PAD, whereas hotels and restaurants positively and significantly influence PAD. Simultaneously, all four variables significantly affect PAD, with an Adjusted R-Square of 70.93%, suggesting that the variables explain most PAD variations, while 29.07% is influenced by factors outside the model. Based on these findings, it is recommended that local governments outside SARBAGITA focus on increasing tourists’ length of stay and strategically developing hotels and restaurants according to zoning regulations to ensure tourism growth is sustainable and minimizes land conversion issues.